Pemanfaatan Ikan Toman (Channa micropeltes) Sebagai Bahan Nugget - Restu Restu (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2012)
The research objective to determine the composition of tapioca-flavored nuggets in order to obtain the ideal and have good nutritional value for consumers. So it can be adopted by communities to diversify processed fishery products. Fish nugget is the product of fish processing by mixed fish meat that has been crushed / milled with tapioca flour and spices, shaped in a baking dish, steamed, cut to the desired size, covered with white egg and panir flour, then fried and ready to eat. The best results based on proximate analysis and organoleptic tests of the product toman fish nugget obtained in treatment A (addition of tapioca 5% of net weight of fish meat), with the value of nutrition: protein 15.89%; karbohitdrat 6.4%, fat 5.45%, water 72.22% and organoleptic value of 7.7 (hedonic scale). Specifications nugget produced (appearance) is clean and attractive, distinctive smell of fish nugget, taste and savory, and quite compact.